Corporate Life Cycle and Dividend Policy after Economic Uncertainty: Is Cash Holding Important for SDG 8? - Estu Widarwati; Nurul Rohmah Rofiah; E. Wityasminingsih (Journal of Current Studies in SDGs, 2026)
Objective: Corporate recovery activities require adequate financial resources to support operations, investments, and business sustainability under both normal and uncertain economic conditions. To examine the mediating role of cash holding in the relationship between the corporate life cycle and dividend policy, providing insights into sustainable financial decision-making that support Sustainable Development Goal (SDG) 8 on sustainable economic growth. Method: Employing a quantitative approach using panel data from 63 non-financial companies listed on the IDX during the 2017–2021 period, resulting in 315 firm-year observations. Corporate life cycle is measured using retained earnings to total assets (RE/TA) and retained earnings to total equity (RE/TE), while dividend policy is proxied by the dividend payout ratio. Panel data regression and the Sobel test are used to test the proposed hypotheses. Results: The findings indicate that dividend policy is significantly influenced by the corporate life cycle. The results also show that cash holding is affected by the corporate life cycle and has a significant positive effect on dividend payments among Indonesian non-financial firms. However, the Sobel test does not provide strong evidence that cash holding mediates the relationship between the corporate life cycle and dividend policy. Novelty: Extending prior literature by examining the mediating role of cash holding in the relationship between corporate life cycle and dividend policy within an emerging market context. The findings highlight the importance of aligning cash management decisions with corporate life cycle stages to support sustainable financial performance, business resilience, and SDG 8.